Genomic investigation of oat quality - Molnar, Stephen J.; Tinker, Nicholas; DeKoeyer, David; Orr, Winson; Lybaert, Anissa; Yan, Weikai; Mather, Diane; Wight, Charlene; McElroy, Art (MTT, 2004)
Both structural genomic and functional genomic approaches increase our understanding of the genetics of quality traits in oats, thereby providing knowledge and tools that accelerate breeding for oat improvement. Initially, we employed the structural genomic approaches of recombination mapping and quantitative trait locus (QTL) analysis to investigate the genetics of a number of quality traits in a Terra x Marion (TM) recombinant inbred population (DeKoeyer et al. 2004). Bi-plot analyses gave complementary insight. These identified genomic regions that play a major role in controlling oil, beta-glucan, and protein content. Comparative marker and QTL mapping with other oat populations increased our understanding of the number and organization of the genes involved and further validated the TM QTLs. Extension to additional elite populations contrasting for these traits helped to complete the analysis. Markers flanking the TM oil and beta-glucan QTLs were converted to sequence characterized amplified region (SCAR) markers (Orr and Molnar 2004). These polymerase chain reaction (PCR)-based markers are robust, rapid, and cost efficient and, therefore, suitable for markerassisted breeding. Recently, functional genomic approaches have been employed to isolate candidate genes in the biochemical pathways for oil and protein content, to study expression level polymorphisms, and to associate both of these with QTLs in mapping populations (Lybaert 2004). These approaches promise to advance our understanding of the involvement of key enzymes in oil and protein biosynthesis and their regulators. DeKoeyer, D., et al. 2004, Theoretical and Applied Genetics 108:(in press); Lybaert, A. 2004, PhD Thesis (in preparation), McGill University; Orr, W. & Molnar, S.J. 2004, (submitted).
Keywords: Ka; oil; beta-glucan; protein; QTL; marker; breeding